Morphological and phylogenetic insights reveal Cucurbitaria berberidicola (Cucurbitariaceae, Pleosporales) as a new species from Uzbekistan - Appadoo, Michée A.; Wanasinghe, Dhanushka N.; Gafforov, Yusufjon; Chethana, K.w. Thilini; Abdurazakov, Aziz; Hyde, Kevin D.; Li, Qirui (Phytotaxa, 2021)
A survey of microfungi in the mountain areas of Uzbekistan revealed several specimens of cucurbitaria-like taxa. In this paper, one new species of Cucurbitaria is described based on a polyphasic approach, including morphological examination and molecular phylogeny. We compared the sexual morph (ascomata, asci, and ascospores) of the specimens collected with known species of Cucurbitaria and carried out multi loci (LSU, ITS, rpb2 and tef1-α) phylogenetic analyses. Cucurbitaria berberidicola sp. nov. is morphologically closely related to Cucurbitaria berberidis (the generic type) and C. oromediterranea. The sequence-based analyses verified a clear distinction, hence supporting the introduction of the new species.